2017
DOI: 10.1037/xhp0000309
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order cognitive control in dual tasks: Evidence from task-pair switching.

Abstract: In the present study, we combined the psychological refractory period (PRP) paradigm with a novel task-pair switching logic which enabled us to isolate performance costs occurring at the global level of task-pairs. In Experiment 1, in which we used conceptually overlapping responses for Task 1 (T1) and Task 2 (T2), we generated 3 task-pairs by combining 1 of 3 visual tasks (T1) with an auditory task (T2). In addition to worse performance after a short SOA than a long SOA (i.e., PRP effect), we found impaired p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 37 publications
3
53
1
1
Order By: Relevance
“…However, in line with the cited evidence for a more flexible, strategic view on cognitive control in multitasking, some researchers explicitly suggested that response order in the PRP paradigm might to some extent be scheduled actively (e.g., De Jong, 1995;Leonhard et al, 2011;Luria & Meiran, 2003;Szameitat, Lepsien, von Cramon, Sterr, & Schubert, 2006). Instead of being determined in a purely stimulus-driven (bottom-up) manner, it was suggested that additional control processes specific to response-order coordination are required, for instance task sequence activation or inhibition processes (e.g., Hirsch, Nolden, Koch, 2017;Sigman & Dehane, 2008). Importantly, most previous research can be characterized as taking a more macroscopic view on response-order control.…”
Section: Temporal Processing Dynamics and Response Scheduling In The mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in line with the cited evidence for a more flexible, strategic view on cognitive control in multitasking, some researchers explicitly suggested that response order in the PRP paradigm might to some extent be scheduled actively (e.g., De Jong, 1995;Leonhard et al, 2011;Luria & Meiran, 2003;Szameitat, Lepsien, von Cramon, Sterr, & Schubert, 2006). Instead of being determined in a purely stimulus-driven (bottom-up) manner, it was suggested that additional control processes specific to response-order coordination are required, for instance task sequence activation or inhibition processes (e.g., Hirsch, Nolden, Koch, 2017;Sigman & Dehane, 2008). Importantly, most previous research can be characterized as taking a more macroscopic view on response-order control.…”
Section: Temporal Processing Dynamics and Response Scheduling In The mentioning
confidence: 99%
“…He found a tendency towards repeating the processing order from the previous trial in the unpredictable stimulus-order condition, indicating contextual modulation of response-order control. Probably, this effect can be explained by the intention to avoid performance costs associated with trial-by-trial switches of response order (Luria & Meiran, 2003;Hirsch, Nolden, & Koch, 2017).…”
Section: Temporal Processing Dynamics and Response Scheduling In The mentioning
confidence: 99%
“…This measure is often interpeted as a marker of inhibitory task control (for reviews, see Gade, Schuch, Druey, & Koch, 2014;Koch, Gade, Schuch, & Philipp, 2010). Hybrids between the different multitasking paradigms have also been developed; for instance, measuring task-switch costs and N-2 repetition costs in a PRP paradigm in order to investigate higher-level task-order control (e.g., Hirsch, Nolden, & Koch, 2017;Kübler, Reimer, Strobach, & Schubert, 2018;Luria & Meiran, 2003;Stelzel, Kraft, Brandt, & Schubert, 2008;Strobach, Soutschek, Antonenko, Flöel, & Schubert, 2015), or to investigate action effect monitoring Wirth, Steinhauser, Janczyk, Steinhauser, & Kunde, 2018).…”
Section: Multitasking Paradigms In Cognitive Psychologymentioning
confidence: 99%
“…In the task-switching domain, there is converging evidence that inhibition is involved in task-switching performance (e.g., Mayr & Keele, 2000; for a review, see, e.g., Koch et al, 2010). In dual-task research, however, inhibition has not yet been examined systematically (see Hirsch, Nolden, & Koch, 2017, for an exception), thus remaining an important topic for future studies.…”
Section: Response Inhibitionmentioning
confidence: 99%